The training and development process for a world-class female handball player: a longitudinal and retrospective case study - Haugen, T.; Bucher Sandbakk, S.; Sandbakk, Ø.; Tønnessen, E. (Frontiers in Sports and Active Living, 2025)
Introduction: Limited information is available regarding the development of young talents who successfully follow the pathway to professional handball. The aim of this study was to retrospectively investigate the longitudinal training and development process of a world-class female handball player.